Bioactive composition, antifungal, antioxidant, and anticancer potential of agarwood essential oil from decaying logs (Gyrinops spp.) of Papua Island (Indonesia) - Asep Hidayat, Maman Turjaman, Ruqoyah Qamyari, Rinaldi Imanuddin, Dudi Tohir, Raden Gunawan Hadi Rahmanto, Arida Susilowati (Journal of Applied Pharmaceutical Science, 2021)
Decaying logs of Gyrinops spp. are an important agarwood source originating from Papua Island and have been exploited since 2004. It is well known as the resinous heartwood used as a pharmaceutical resource and was listed under the trading name “filaria” before 2020. The bioactive and chemical composition of agarwood essential oil (AEO) from decaying logs (Gyrinops spp., M1) was studied to ensure its potential in comparison with AEO from a 1.5-year-old inoculated agarwood tree (M2) and that of ordinary commercial AEO (M3). The chemical composition analyzed by the retention index showed that M1 had quite a similar profile to that of M2, while M1 was different from M3. Ten compounds in M1 were responsible for determining specific agarwood odor: agarospirol, dehydrojinkoh-eremol, baimuxinal, selina-3,11-dien-9-ol, selina-3,11-dien-14-al, selina-3,11-dien-14-ol, selina-4,11-dien-14-al, guaia-1(10),11-dien-15-ol, dihydrokaranone, and guaia-1(10),11-dien-15-al. The AEO of M1 had higher inhibition to the growth of Fusarium solani and showed the highest antioxidant activities compared to AEO of M2 and M3. Furthermore, all AEOs showed anticancer properties against breast cancer (MCF-7) in the range from 0.8% to 15.1% at the concentration of 0.1 mg ml−1. This study indicated that decaying logs (Gyrinops spp.) had antifungal, antioxidant, and anticancer potentials and could be further used as pharmaceutical resources.
Keywords: Gyrinops, gaharu, distillation, fungal-induction, volatile compounds